The Removal of Basic Blue 41 Dye from Aqueous Solutions by Bituminous Shale - Ali E. Müftüoglu; Bektas Karakelle; Mehmet Ergin; Ali Y. Erkol; Faruk Yilmaz (Adsorption Science & Technology)
The removal of Basic Blue 41 dye from aqueous solutions was investigated using bituminous shale as an adsorbent. The parameters studied in batch experiments were the effect of contact time, temperature, particle size and adsorbate concentration. The adsorption was found to follow a first-order process. Equilibrium adsorption data were obtained at three different temperatures, i.e. 25°C, 40°C and 50°C, and with particle sizes corresponding to the following meshes: 45–120, 120–230, 230–325 and 325–400. The resulting experimental equilibrium data were well represented by the Langmuir isotherm. It was found that the smaller the particle size, the higher the adsorption. The adsorption capacity increased with temperature.